Differences in perceived health status outcomes among heterosexual, homosexual (gay or lesbian) and bisexual Korean adolescents (2014)
The purpose of this study was to examine differences in perceived health status outcomes among heterosexual, homosexual (gay or lesbian), and bisexual Korean adolescents. Originally, in 2012, over 70,000 adolescents aged 12–18 years participated in the Eighth Korea Youth Risk Behavior Webbased Survey (KYRBWS-VIII). However, only 11,829 adolescents provided information on their sexual experiences and behaviors, such as kissing, fondling, and sexual orientations, i.e., homosexual (gay or lesbian), bisexual, or heterosexual. Therefore, data from only 11,829 adolescents surveyed were analyzed using a one-way analysis of variance, with a Scheffe post-hoc test, to determine the differences in perceived health status outcomes among Korean adolescents of the different sexual orientation groups. Boys across all 3 groups showed significant differences in general health status (p = 0.004), happiness (p = 0.045), and getting sufficient sleep (p = 0.004). Further, Scheffe post-hoc comparisons of group mean scores revealed that homosexual (gay) boys had poorer overall health (p = 0.004) and bisexual boys had less sufficient sleep (p = 0.017); however, there were no significant differences in happiness between homosexual (gay) (p = 0.651) and bisexual boys (p = 0.064) as compared to heterosexual boys. Moreover, there were no significant differences in general body shape (p = 0.320) and oral health (p = 0.549) among the 3 groups we studied. Girls differed significantly in general body shape (p = 0.026) across all 3 groups in the results of the one-way ANOVA we performed. However, according to Scheffe post-hoc analyses, no significant differences existed in general body shape among girls in both the homosexual (lesbian) and bisexual groups (p = 0.112 and 0.204, respectively). Additionally, there were no significant differences in general health status (p = 0.113), happiness (p = 0.602), oral health (p = 0.290), and getting sufficient sleep (p = 0.481) among adolescent girls in all 3 groups. From these results, we concluded that, in general, homosexual (gay or lesbian) and bisexual Korean teens do not differ significantly from heterosexual Korean teens in perceived health status outcomes.